1997
DOI: 10.1093/bja/78.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane increases the uptake of glutamate in synaptosomes from rat cerebral cortex

Abstract: We have studied the effect of increasing concentrations of isoflurane on high- and low-affinity uptake of L-glutamate using synaptosomes from rat cerebral cortex. In the high-affinity uptake range, 0.5% isoflurane had no effect on uptake velocity, while 1.5% and 3.0% isoflurane caused an increase in mean Vmax to 131 (SEM 54) and 210 (103)% of control, respectively. There was no significant change in the K(m) value. Vmax and K(m) values for low-affinity uptake of L-glutamate were unchanged by 1.5% isoflurane. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This process is enhanced by volatile anesthetics such as isoflurane (Larsen et al, 1997;Zuo, 2001;Huang and Zuo, 2003) and halothane (Miyazaki et al, 1997). Blockage of glutamate uptake leads to an increased demand of anesthesia (Cechova and Zuo, 2006), which is used to counteract increasing excitatory signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process is enhanced by volatile anesthetics such as isoflurane (Larsen et al, 1997;Zuo, 2001;Huang and Zuo, 2003) and halothane (Miyazaki et al, 1997). Blockage of glutamate uptake leads to an increased demand of anesthesia (Cechova and Zuo, 2006), which is used to counteract increasing excitatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this impairment may be the action of isoflurane on an enhancement of glutamate uptake by specific glial GLT1/EAAT2 transporters (Larsen et al, 1997;Zuo, 2001) and the consequent reduction of excitatory neuronal inputs to inhibitory interneurons. The idea behind this reasoning is that a reduction in excitation would result in a diminished inhibitory drive.…”
Section: Pharmacological Correlates Of Inhibition During Bsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsen et al (1997) showed that isoflurane increased glutamate uptake in synaptosomes prepared from rat cerebral cortex. However, using a similar experimental model, Nicol et al (1995) failed to demonstrate any increases in glutamate uptake by isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…The in¯uence of the general anaesthetics on this process, however, is not fully understood. Recent studies (Larsen et al, 1997;Miyazaki et al, 1997) suggest that volatile anaesthetics at clinical concentrations can potentiate glutamate uptake into synaptosomes and astrocytes.…”
Section: Introductionmentioning
confidence: 99%